Biochemical changes induced by compost tea and seaweed formulation spray inhibiting Alternaria leaf blight of sunflower: Biochemical changes induced by compost tea and seaweed formulation spray inhibiting Alternaria leaf blight of sunflower - M SHADAB; K KHATIB; K KARUNA; C P MANJULA; DATTATREYA (Journal of Oilseeds Research, 2020)
Compost tea and seaweed extract were tested against Alternaria blight of sunflower. Foliar spray of compost tea (1:10) @ 30, 45 DAS and propiconazole @ 1 ml/l at 60 DAS was effective in controlling the Alternaria blight of sunflower with least disease severity which was on par with foliar spray of seaweed formulation at 30, 45 DAS and propiconazole at 60 DAS. The defense enzymes such as superoxide dismutase, peroxidase, secondary metabolites such as phenolics and flavonoids increased in foliar spray of compost tea and also in propiconazole treated plants.